2014
DOI: 10.1098/rspb.2014.1146
|View full text |Cite
|
Sign up to set email alerts
|

Paternal care in a fish: epigenetics and fitness enhancing effects on offspring anxiety

Abstract: In many animals, including humans, interactions with caring parents can have long-lasting effects on offspring sensitivity to stressors. However, whether these parental effects impact offspring fitness in nature is often unclear. In addition, despite evidence that maternal care can influence offspring behaviour via epigenetic alterations to the genome, it remains unclear whether paternal care has similar effects. Here, we show in three-spined sticklebacks, a fish in which fathers are the sole provider of offsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 34 publications
1
55
0
1
Order By: Relevance
“…Thus, previous predator experiences of mothers can influence offspring traits and survival both directly [12,13,21] and indirectly through how these experiences affect paternal care (this study). Paternal care in this species affects offspring behavioural [26,28,29] and morphological [26] development, brain gene expression [28] and is linked to offspring survival with predators [28]. Whether paternal care can compensate for the negative effects of maternal predator exposure on offspring, or complements these maternal effects, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, previous predator experiences of mothers can influence offspring traits and survival both directly [12,13,21] and indirectly through how these experiences affect paternal care (this study). Paternal care in this species affects offspring behavioural [26,28,29] and morphological [26] development, brain gene expression [28] and is linked to offspring survival with predators [28]. Whether paternal care can compensate for the negative effects of maternal predator exposure on offspring, or complements these maternal effects, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The fish hatchery environment and management practices used to raise fish can produce stable, heritable, nongenetic changes in fish (Salinas and Munch ; Evans et al. ; McGhee and Bell ; Shao et al. ; Jonsson and Jonsson ).…”
Section: Why Production Management Is Counterproductivementioning
confidence: 99%
“…While recent studies are documenting the important consequences of paternal stress prior to conception on offspring brain development [31] and HPA axis regulation [32,33] potentially via changes in DNA methylation in sperm [34], these are some of the first data to show that fathers, like mothers, can influence their offspring post-fertilization. Furthermore, we have found that father care alters expression of a gene responsible for de novo methylation (DNMT3a) in offspring brains [35], suggesting that paternal care might have long-lasting effects on offspring behavior via DNA methylation.…”
Section: Effects Of Paternal Stress On Offspring Outcomes In Sticklebmentioning
confidence: 99%